Certain Studies On Zoonyms In Linguistics (Texas Journal of Philology, Culture and History, 2024)
This article discusses the study of zoonyms in world and Uzbek linguistics. Detailed opinions are expressed about the content and essence of the scientific research conducted by linguists on lexemes with the archetype "hayvon (animal)", their meaningful field, proverbs with a zoonym component, and phraseologisms. These scientific works are compared with each other.